Ethics of Social Service Organizations (part II) - Pelegrí Viaña, Xavier (Cuadernos de Trabajo Social, 2013)
This article, by extension, was divided into two parts. The first, published in the previous issue, focused on discovering the characteristics of both welfare organizations, and ethics as applied to the organization. In this second part, we present a scheme to locate and analyse the ethical dimension in social service organizations as well as the position that, in them, correspond to the professionals take. This is intended to establish the desirability of introducing or further ethical reflection in social service organizations and provide arguments that also concerns they raised and keep the utmost honest type of behaviour, in keeping with the dignity of everyone and enabler of a good life.